Chronicprofile: um modelo de gerenciamento de perfis dinâmicos orientado a doenças crônicas não transmissíveis - Marques, Emerson Butzen (Universidade do Vale do Rio dos Sinos, 2018)
The contemporary scenario of noncommunicable chronic diseases (NCDs) is challenging. According to the latest report of the World Health Organization (WHO), in the global context, 38 million of deaths are a consequence of such diseases. For 2030, the number is expected to increase 52 million. Besides, the internet access and the proliferation of mobile devices, such as smartphones, are tools that facilitate the control and autonomous follow-up of patients. Furthermore, context-aware systems refer to transparent solutions for collecting users data that allow the identification of daily habits of individuals, which can be decisive in the treatment of diseases. The dynamic profile is a creation and automatic maintenance based on information and user Activities conforms the time cite Valmorbida2014. Therefore from detected contexts, profiles are defined, and the conversion between the two provides recommendations of personalized features to the patient. Considering this set of information, the research question is defined : how a model based on of Ubiquitous Computing could be designed to manage dynamic profiles in the monitoring of patients with NCDs? The study argue that those profiles supports the diseases control, allow the self-management and the organization of the patient specially about his proper nutrition, physical activities, biological indicators, glycaemic indices and behavioral risks. The profiles composition derives from information about the patient’s chronic conditions, such as: pressure, blood glucose, waist (WHR), weight, among others, besides the behavioral aspects, as medication intake, physical activities, etc. The study aims to create a module for dynamic profile management, focused on the attention to NCDs. The conduction of this research considers two cases from bearers patients of acute coronary disease (ACD), the main cause of death in modern societies. The literature review covers investigations about u-Health solutions (CACERES et al., 2006), of profiles and risk factors for noncommunicable chronic diseases. This applied research is centered in the proposition of a model called ChronicProfile, integrated to U’Ductor model (VIANNA; BARBOSA, 2014). The study was carried out with the partnership of PPG in Collective Health, from Unisinos, to collect data from the patients in follow-up, through the application created in the course of this research. The prototype implementation involves the follow components : 1) the web application « Meu Cuidador Plano de Cuidado », dedicated to medical utilization to register the care plan ; 2) the Android application « MeuCuidador », designed to patients to register informations about their daily activities. The application modules implies historic contexts selection and processing, the inference and generation of profiles, besides the specific data bases. The modules viability evaluation derives from two experimentals. First, real contexts from patients with some ACD were analysed to verify differences between profiles and the improvement of their chronic conditions. Secondly, the prototype capacity was evaluated to the generation of a dynamic profile to a same patient by inserting a new risk factor to be monitored. Among the results, the main one implies ChronicProfile’s data evaluation from historical contexts and care plans from specialists that permits monitoring and measurement of patient curent conditions, and also the NCDs risk factos of evolution or involution.
Keywords: Computação Ubíqua; Computação móvel; Gerenciamento de doenças crônicas; Perfil dinâmico; Ubiquitous computing; Mobile computing; Chronic disease management; Dynamic profile; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação